2020
DOI: 10.3390/cancers12092480
|View full text |Cite
|
Sign up to set email alerts
|

CDK4/6 Inhibitors in Hormone Receptor-Positive Metastatic Breast Cancer: Current Practice and Knowledge

Abstract: Treatment paradigms in advanced hormone receptor (HR)-positive breast cancer were substantially transformed with cyclin-dependent kinase 4 and 6 inhibitors (CDK4/6i) approval. The addition of these drugs to endocrine treatment profoundly improved progression-free and overall survival. Additionally, other important endpoints, such as the response rate, time to chemotherapy, and a delay in quality of life deterioration, were positively impacted by CDK4/6 inhibitors’ addition to the treatment of advanced HR-posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 75 publications
(92 reference statements)
0
21
0
Order By: Relevance
“…Currently there is no tool for early response assessment in patients with metastasized breast cancer undergoing CDK4/6 inhibitor therapy. Depending on the treatment line and the presence of visceral metastasis or endocrine resistance, the median PFS is <10 months, with up to 40% of patients having PD during the first 6 months of treatment [10, 16]. Moreover, CDK4/6 inhibitor therapy causes significant adverse reactions and high treatment costs, making early response assessment an important clinical issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently there is no tool for early response assessment in patients with metastasized breast cancer undergoing CDK4/6 inhibitor therapy. Depending on the treatment line and the presence of visceral metastasis or endocrine resistance, the median PFS is <10 months, with up to 40% of patients having PD during the first 6 months of treatment [10, 16]. Moreover, CDK4/6 inhibitor therapy causes significant adverse reactions and high treatment costs, making early response assessment an important clinical issue.…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains unclear which patients will benefit from CDK4/6 inhibitor therapy. Predicting the response to CDK4/6 inhibitor therapy is of great importance given the high rate of side effects like neutropenia, diarrhea, and alopecia, the high treatment costs, and the possibility of initiating alternative therapy at an early time point [10].…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with AE reports from clinical trials. 37 Surveys indicated that patients’ average total symptom burden was slightly to moderately bothersome, and average fatigue scores exceeded the cutoff for severe fatigue. 33 Of note, it may not always be possible for patients to tease apart symptoms caused by their disease versus CDK4/6 inhibitors versus other treatments such as endocrine therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of cyclin-dependent kinases (CDKs) enables cell cycle progression, representing the hallmark of cancer pathological development. The most important drivers of cell cycle proliferation are known to be CDK4/6 (3). Recently, the US Food and Drug Administration, the European Medicine Agency and the Saudi Food and Drug Administration (SFDA), approved three highly selective inhibitors of CDK4/6 for (HR + /HER2 -) advanced metastatic breast cancer, namely (palbociclib, ribociclib and abemaciclib) (4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%